2,2′-Bipyridin-1-ium hemioxalate oxalic acid monohydrate - Błażej Dziuk; Anna Jezuita (IUCrData, 2018)
The asymmetric unit of the title compound, C10H9N2+·0.5C2O42−·C2H2O4·H2O, consists of a 2,2′-bipyridinium cation, half an oxalate dianion, one oxalic acid and one water molecule. One N atom in 2,2′-bipyridine is unprotonated, while the second is protonated and forms an N—H...O hydrogen bond. In the crystal, the anions are connected with surrounding acid molecules and water molecules by strong near-linear O—H...O hydrogen bonds. The water molecules are located between the anions and oxalic acids; their O atoms participate as donors and acceptors, respectively, in O—H...O hydrogen bonds, which form sheets arranged parallel to the ac plane.